2015
DOI: 10.1016/j.ejro.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric CT perfusion assessment of treatment response in head and neck squamous cell carcinoma: Comparison of CT perfusion parameters before and after chemoradiation therapy

Abstract: Background and purposeWorld Health Organization estimated that there were 600,000 new cases of head and neck cancers and 300,000 deaths each year worldwide. Scientific modalities to predict the treatment outcomes are not available yet. We conducted this study to (1) compare CT perfusion parameters before and after chemoradiation among patients with head and neck squamous cell carcinoma and (2) to evaluate the prognostic value of each perfusion parameter in predicting the response to chemoradiation.Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…In theory, tumours from different tissues or different pathological types of the same tumour can be identified using these parameters. CT perfusion imaging has been used in the differential diagnosis of squamous cell carcinoma of the head and neck, as well as in the prognosis and posttreatment response evaluation of neck lymphoma [27][28][29] . Each pure substance has a specific spectral attenuation curve, and X-ray attenuation in various tissues can be expressed by a pair of known pure substances 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…In theory, tumours from different tissues or different pathological types of the same tumour can be identified using these parameters. CT perfusion imaging has been used in the differential diagnosis of squamous cell carcinoma of the head and neck, as well as in the prognosis and posttreatment response evaluation of neck lymphoma [27][28][29] . Each pure substance has a specific spectral attenuation curve, and X-ray attenuation in various tissues can be expressed by a pair of known pure substances 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies included mixed tumour sites while two studies reported the role of pCT in OPC . Serial scans including mid‐treatment scans were performed in three studies while two studies reviewed the utility of pCT after induction chemotherapy to decide whether primary surgery or primary RT would be performed. All studies showed significant association between at least one parameter tested with the endpoints (response to therapy, LC or survival).…”
Section: Resultsmentioning
confidence: 99%
“…Prior literature has shown that CT perfusion features are promising for assessing treatment response with chemoradiation [14,15]. A study prospectively conducted by Rana et al [14] evaluated neck CT perfusion characteristics in 24 patients and found that blood flow alone was 83.3% predictive of response to chemoradiation irrespective of stage.…”
Section: Discussionmentioning
confidence: 99%